The complete mitochondrial genome of the Forrest’s rock squirrel (Sciurotamias forresti, Rodentia: Sciuridae) and its phylogenetic implication - Mengru Xie; Hongwei Zhou; Yongyuan Li; Wenge Dong; Xianguo Guo; Chengfu Zhao; Wenyu Song (Mitochondrial DNA. Part B. Resources)
We sequenced the whole mitochondrial genome of Sciurotamias forresti using Illumina, revealing a 16,534 bp circular genome with 13 protein-coding genes (PCGs), 22 tRNAs, 2 rRNAs, a D-loop, and OL. Base composition: 32.95% A, 28.63% T, 26.14% C, 12.28% G. Phylogenetic analysis of 25 Sciuridae species showed a deep split between Sciurotamias forresti and Sciurotamias davidianus, more distant than those between other genera in the subfamily Xerinae. This supports the notion that Sciurotamias forresti may be ranked as a genus and indicated the necessity of further studies integrating morphological comparison and divergence dating to reevaluate its taxonomic position.